2019
DOI: 10.1108/ijppm-04-2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of the Indian non-life insurance sector

Abstract: Purpose The purpose of this paper is to analyse the performance of the Indian non-life (general) insurance sector in terms of total factor productivity (TFP) over the period 2005–2016. Design/methodology/approach This study utilises Färe‒Primont index (FPI) to access the change in TFP and its components: technical change, technical efficiency and mix and scale efficiency over the observation period. Moreover, it employs the Mann–Whitney U-test to scrutinise the difference between the public and the private i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…The first study [17] found that the Indian non-life insurance industry was moderately technical, scaled, cost-effective, and allocatively efficient. The second study [18] found (using the Fare-Primont index) that the non-life insurance sector exhibited a very low level of total factor productivity. The total factor productivity growth observed during the observed period (2005-2016) is mainly attributable to scale-mix efficiency.…”
Section: Indian Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The first study [17] found that the Indian non-life insurance industry was moderately technical, scaled, cost-effective, and allocatively efficient. The second study [18] found (using the Fare-Primont index) that the non-life insurance sector exhibited a very low level of total factor productivity. The total factor productivity growth observed during the observed period (2005-2016) is mainly attributable to scale-mix efficiency.…”
Section: Indian Studiesmentioning
confidence: 98%
“…In a second study, Sinha [16] estimated the efficiency of Indian general insurance companies for 2013-14 using the conditional performance benchmarking method. Ilyas and Rajasekharan [17,18] estimated the efficiency, total factor productivity and returns to scale of the Indian non-life insurance industry over the period 2005-2016. The first study [17] found that the Indian non-life insurance industry was moderately technical, scaled, cost-effective, and allocatively efficient.…”
Section: Indian Studiesmentioning
confidence: 99%